2009
DOI: 10.1088/0957-4484/20/37/375705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of B/N co-doping on the stability and electronic structure of single-walled carbon nanotubes by first-principles theory

Abstract: The stability and electronic structure of single-walled carbon nanotubes with B/N co-doping are investigated in detail by using the first-principles theory. From eight possible B/N co-doping configurations, it is found that the one with substitutional B and N atoms located at neighboring sites has a smaller formation energy than that with separate B/N atoms. The electronic structure of armchair carbon nanotubes evolves from metallic to semiconducting as a result of B/N co-doping, whereas the energy gaps of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…The stability of the Cu-chain-SWCNT was evaluated by calculating the formation energy ( E f ), which is defined by the following equation 35 , 36 : where E dop and E SWCNT is the total energy of the Cu-chain-SWCNT and pristine SWCNT, respectively; μ (Cu) is the chemical potential of a Cu atom, calculated from the isolated Cu atom (in a 20 × 20 × 20 Å lattice) using DMOL 3 code 37 ; n(C) and n(Cu) are the number of C atoms in the pristine SWCNT and Cu atoms in the Cu-chain-SWCNT, respectively. The stability of doped SWCNT can be evaluated using the formation energy; the more negative the formation energy, the more stable they should be 35 , 37 39 . The calculated E f of the Cu-chain-SWCNT is −0.325 eV/atom, indicating that the Cu-chain-SWCNT is energetically favorable.…”
Section: Resultsmentioning
confidence: 99%
“…The stability of the Cu-chain-SWCNT was evaluated by calculating the formation energy ( E f ), which is defined by the following equation 35 , 36 : where E dop and E SWCNT is the total energy of the Cu-chain-SWCNT and pristine SWCNT, respectively; μ (Cu) is the chemical potential of a Cu atom, calculated from the isolated Cu atom (in a 20 × 20 × 20 Å lattice) using DMOL 3 code 37 ; n(C) and n(Cu) are the number of C atoms in the pristine SWCNT and Cu atoms in the Cu-chain-SWCNT, respectively. The stability of doped SWCNT can be evaluated using the formation energy; the more negative the formation energy, the more stable they should be 35 , 37 39 . The calculated E f of the Cu-chain-SWCNT is −0.325 eV/atom, indicating that the Cu-chain-SWCNT is energetically favorable.…”
Section: Resultsmentioning
confidence: 99%
“…where E tot is the total energy of the BC 2 N nanotubes; (B), (C), and (N) are the chemical potential of single B, C, and N atoms obtained by calculating the total energy per atom of ␣-boron phases, single free carbon atom and ␣-nitrogen phases [43], respectively; n(B), n(C), and n(N) are the number of B, C, and N atoms in BC 2 N nanotubes, respectively. …”
Section: Theoretical Methodsmentioning
confidence: 99%
“…We defined two different styles of bond for zigzag and armchair nanotubes. As shown in Figure 3, ⊥ represents the bond that perpendicular to the tube axis, represents the bond that parallel to the tube axis (the method has been employed in previous paper [43]). For BC 2 N nanotubes ZZ-d and ZZ-e, the average bond length of C B⊥ and B N⊥ became larger than C C⊥ and C N⊥ obviously, resulting in tube ZZ-d has an oval cross section and the structure of tube ZZ-e was also changed slightly.…”
Section: Structurementioning
confidence: 99%
“…N. Saikia et al proposed SWCNT as a drug carrier to the target area [ 182 ]. As the Si doping in the CNT is less reported in the literature than the B/N doping, better electronic properties of Si lead them to use Si-doped SWCNT to carry the INH drug using DFT theory and molecular docking [ 84 , 183 ]. In a Van der Waals interaction corrected investigation it was found that INH parallel to the (5, 5) SWCNT have better stability with more adsorption energy of 15.59 kcal/mol compared to the perpendicular alignment of the INH with (5, 5) SWCNT with an adsorption energy of 13.65 kcal/mol.…”
Section: Carbon-based Ldns For Drug Delivery and Sensing Applicationsmentioning
confidence: 99%